HUBUNGAN PENGETAHUAN DAN KOMUNIKASI PERAWAT DENGAN PELAKSANAAN PERENCANAAN PULANG DI RUANG RAWAT INAP RSUD ZAINAL ABIDIN PAGARALAM WAY KANAN - Teguh Pribadi; M. Ricko Gunawan; Djunizar Djamaludin (Universitas Malahayati Lampung, 2019)
ABSTRACT : THE RELATIONSHIP KNOWLEDGE AND NURSING COMMUNICATION WITH THE IMPLEMENTATION OF PATIENT RECOVERY PLANNING INPATIENT RSUD ZAINAL ABIDIN PAGARALAM WAY KANAN 2018 Background: In Indonesia, as many as (61%) nurses in Yogyakarta do not undertake home planning. In addition, research conducted in Bandung showed that as many (54%) nurses did not carry out the planning home. In Lampung Province, especially in Zainal Abidin Pagaralam Way Kanan Hospital, based on observation of the list of outgoing patients, not all nurses write home plans for the patients. Only 32 list (25%) of the 128 list of information have been made back home (Medical Record of RSUD Zainal Abidin Pagaralam Right Way, 2017).Purpose: To know the relationship of knowladge and nurse communication with the implementation of planning to go home in hospital room of Zainal Abidin Pagaralam Hospital Right Way of Year 2018.Methods: The type of this research is quantitative, the design in this study used the design of Analytic Survey with cross sectional approach, the number of population and the sample of 72 people, the sample technique in this study is the total sampling. The research will be conducted at RSUD Zainal Abidin Pagaralam Way Kanan Year 2018, with questionnaire research instrument and statistic test using chi-square test.Results: In this research, it was found that 38 (73,7%) were not good enough and 10 (26,3%) were good implementation with p-value (0,001) and 37 respondents had bad communication obtained 28 (75,7%) the implementation is not good and 9 (24,3%) the implementation is good with p-value (0.000).Conclusion: There is a Significant Relation Between Nursing Knowledge and Communication With Implementation of Planning Home in the Inpatient Room of Zainal Abidin Pagaralam Hospital Right Way of Year 2018. The suggestion in this research is to prepare in planning the making of standard policy guideline for planning the return home. Keywords : Pediatric Communication, Implementation, Planning Home